Weimar : a jurisprudence of crisis - Jacobson, Arthur J.; Schlink, Bernhard (University of California Press, 2000)
This selection of the major works of constitutional theory during the Weimar period reflects the reactions of legal scholars to a state in permanent crisis, a society in which all bets were off. Yet the Weimar Republic's brief experiment in constitutionalism laid the groundwork for the postwar Federal Republic, and today its lessons can be of use to states throughout the world. Weimar legal theory is a key to understanding the experience of nations turning from traditional, religious, or command-and-control forms of legitimation to the rule of law. Only two of these authors, Hans Kelsen and Carl Schmitt, have been published to any extent in English, but they and the others whose writings are translated here played key roles in the political and constitutional struggles of the Weimar Republic. Critical introductions to all the theorists and commentaries on their works have been provided by experts from Austria, Canada, Germany, and the United States. In their general introduction, the editors place the Weimar debate in the context of the history and politics of the Weimar Republic and the struggle for constitutionalism in Germany. This critical scrutiny of the Weimar jurisprudence of crisis offers an invaluable overview of the perils and promise of constitutional development in states that lack an entrenched tradition of constitutionalism.
Keywords: Constitutional history -- Germany -- Sources.; Constitutional law -- Germany -- Philosophy -- History -- Sources.; State, The -- History -- Sources.; Germany -- Politics and government -- 1918-1933 -- Sources.; Droit constitutionnel -- Allemagne -- Philosophie -- Histoire -- Sources.; État -- Histoire -- Sources.; Allemagne -- Politique et gouvernement -- 1918-1933 -- Sources.; LAW -- Constitutional.; LAW -- Public.; PHILOSOPHY -- Political.; Constitutional history; Constitutional law -- Philosophy; Politics and government; State, The; Germany; 1918-1933; Sources; History